Design and development of a high efficiency modulated Class E amplifier - Crafford, Crafford, Hendrik Lambert Helberg Hendrik Lambert Helberg (My University, 2006)
Amplitude modulation is not commonly associated with effective amplifying. This work focuses on implementing amplitude modulation into a high efficiency Class E amplifier. Different types of amplifiers are compared with each other, to show the advantages of using a Class E amplifier. The theory of the Class E amplifier is dealt with in detail. A harmonic filter is designed for the amplifier to make it radio spectrum friendly. The modulation process is implemented with the aid of a transformer into the Class E amplifier. The advantage of this is that the transformer serves both as a radio frequency choke for the Class E circuit as well as a modulator. The implementation of the amplitude modulation into the high efficient Class E circuit was successful. The final Class E circuit had superb efficiency, the harmonic filter showed good harmonic attenuation and the modulation process had low distortion. All this resulted in a fine low power AM transmitter.
M. Tech. (Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology
Keywords: Class E amplifier; Amplifiers; Transformers; 621.384; Audio amplifiers